Risk factors in pediatric melanoma: a retrospective study of 39 cases. Issue 6 (December 2021) - Fidanzi, Cristian; Manzo Margiotta, Flavia; Spinelli, Claudio; Janowska, Agata; Dini, Valentina; Oranges, Teresa; Romanelli, Marco; Morganti, Riccardo; Viacava, Paolo; D'Erme, Angelo M.; Bagnoni, Giovanni
Abstract : Pediatric melanoma is a rare form of the tumor whose epidemiology is widely increasing thanks to the improvement of dermoscopic and anatomopathologic diagnostic techniques. Although it is a tumor of considerable interest in adults, little has been described about the pediatric field. The objective of our study was then to identify the possible risk factors for the development of melanoma in the pediatric population. We performed a retrospective study conducted in the Melanoma and Skin Cancer Unit and Unit of Dermatology (Livorno, Italy). We analyzed a population of 38 children under 21 years with a diagnosis of melanoma. This population was compared with a control population of 114 children followed up in our dermatologic clinic. From our combined univariate-multivariate statistics analysis, the number of nevi [regression coefficient (RC) of 1.04 and odds ratio (OR) of 2.8 confidence interval (Cl, 1.2–6.6)], and family history of melanoma [RC of 1.99 and OR of 7.3 (Cl, 2.3–22.7)] emerged as possible risk factors for the development of melanoma. The identification of these elements would allow the physician to carry out a more targeted preliminary assessment of the patient, potentially decisive in cases of diagnostic doubt of the lesion. Our study also lays the foundations for identifying those children who, despite not having received a diagnosis of melanoma on histologic examination, should be considered as patients susceptible to a focused follow-up, because of the presence of the risk factors that emerged from our research.